RED TAPES IN THE SPHERE OF SCIENCE AND EDUCATION - E. I. TRUBNIKOVA (Высшее образование в России)
The article examines the regulatory burdens of the higher education sphere of Russia. The term «Red Tape» in modern economic literature is associated with presence of excessive regulatory requirements that cause waste of time and financial resources and do not provide benefits to society. Red Tapes mean excessive, meaningless paperwork, high degree of formalization and limitations, unnecessary procedures and numerous inefficient regulatory elements. The permanent reformation of the Russian education sector incorporates a broad range of regulatory requirements that lead to ambiguous results in the regulated sphere. The article analyzes possible purposes of the regulator and outcomes of these government interventions. The analysis shows that the attempts of achieving quantitative indicators have a negative impact on the regulated sphere of science and education. The aim of the article is to expose the negative outcomes of the bureaucratic mechanism, namely Red Tapes in the normative documents for possible regulatory intervention and modification.